Therapeutic proposals of the SUS after suicide attempt in Brazil - Lopes , Tiago Moreno Roberto; Filho , Gerardo Maria de Araújo; Silva, Beatriz Caroline; Oliveira, Matheus Pinheiro de; Oliveira, Larissa Rodrigues de; Zanolla, Layra Silva; Barbosa , Paola Layane Mello; Oliveira , Elimeire Alves de; Araújo , Bruno Pontes de (Seven Editora, 2023)
Suicide is the phenomenon that has been most addressed in society, since its numbers have increased significantly in recent years, drawing the attention of researchers and government officials to possible interventions in public health. Therefore, the present work aims to investigate the therapeutic proposals after suicide attempts in the services offered by SUS - Unified Health System - through exploratory bibliographic research in national sources. The research aims to understand which proposals are directed to these patients who are in a situation of vulnerability, in view of the high rates and incidences after suicide attempts. With this work, it is intended to contribute to the scientific production in Brazil and possible directions of the reception of the individual who attempted the act of suicide. DOI:https://doi.org/10.56238/innovhealthknow-002